Making space for community energy: landed property as barrier and enabler of community wind projects - R. Wade; R. Wade; D. Rudolph (Geographica Helvetica, 2024)
Renewable energy infrastructures, such as wind and solar farms, require land on which they can be deployed. While politics and conflicts over accessing land for renewables are well documented, the role, conditions and potential agency of landownership have been often overlooked or oversimplified as a powerful terrain in the field of renewables development. In this paper, we explore the relationship between landed property and community renewable energy projects. In particular, we focus on how landed property variously influences the development modes of renewables by acting as a mediator, barrier and enabler for different types of wind energy projects. We show how this takes place through appropriation of rents in processes of assetisation and value grabbing by landowners. In this way, value grabbing acts as a vital intermediary process to understand green grabbing and wider processes of capital accumulation through renewables. We draw on insights from the Netherlands and Scotland to illuminate different mechanisms, social and historical conditions, and policies through which landed property constrains or enables community wind energy projects. The paper finishes by sketching out some alternative ways of allocating land for the deployment of renewable energy projects, which could help shift the balance of power in favour of community energy developments.